The utilization of Konjac as Smart Biodegradable Film Packaging with Butterfly Pea Flower Extract and Eggshell Flour as Active Agent: Pemanfaatan Konjac sebagai Smart Biodegradable Film Packaging dengan Bahan Aktif Ekstrak Bunga Telang dan Tepung Cangkang Telur Ayam - Suryadi, Cherry Keiko Alendra; Setijawaty, Erni; Utomo, Adrianus Rulianto; Jati, Ignasius Radix A.P. (JITIPARI, 2024)
This research investigates the effect of adding active ingredients such as butterfly pea flower extract and eggshell powder on the physical and chemical properties of smart biodegradable film packaging. The butterfly pea flower extract was prepared by mixing dry butterfly pea flowers with water in ratios of 0 (without butterfly pea flowers, as a control), 1:250, and 1:125. The eggshell powder was added in concentrations of 0%, 0.15%, and 0.3% (w/v). The result shows that the addition of active agents affected the water vapor transmission rate (WVTR), tensile strength, and elongation of the film. The addition of eggshell powder did not have any significant effect on the total phenol content, anthocyanin content, and antioxidant activity. The smart biodegradable film packaging produced in this study showed total phenol values ranging from 237,8858-907,1768 mg GAE/100 g sample, total anthocyanin content 0.1045-2.3512 mg cy-3-glu eq/100 g sample, antioxidant activity 5,1198-54.8475%, WVTR 60,5826-91,3325 g/m2/24 hours, tensile strength 2,615-8,479 N/mm2/24 hours, and elongation 1,437-43,360%. The results of this study show that the smart biodegradable film packaging developed can be used as an indicator to monitor changes in the quality of steamed chicken meat during storage.